Community Participation in the Process of Forming Village Regulations in Segeri District, Pangkajene and Kepulauan Regency - Bahar, Elma Amalia (Actual Insight, 2025)
Community participation is a crucial element in the process of formulating village regulations. However, in practice, community participation is often neglected. This study aims to analyze (1) the process of formulating village regulations in Parenreng Village, Segeri District, Pangkajene and Kepulauan Regency, (2) the level of community participation in the formulation of village regulations, and (3) the factors influencing community participation in this process. A qualitative approach was employed in this study, with data collection methods involving interviews and documentation. The findings reveal that (1) the process of formulating village regulations in Parenreng Village consists of five stages: planning, drafting, discussion, ratification, and promulgation. In accordance with the Ministry of Home Affairs Regulation No. 111 of 2014, during the planning and drafting stages, the village government has provided space for community participation. (2) However, community participation in the formulation of village regulations in Parenreng Village remains suboptimal and limited. (3) Several factors contributing to the low level of participation include the limited number of community members invited to participate, inadequate transportation facilities, the development of apathetic attitudes within the community, individual busyness, and the less-than-optimal functioning of members of the Village Representative Body.